Idiopathic ulcerative colitis and fecal calprotectin as a marker of remission - Lorena Batista da Silva, Raiza; Franco Nara, Janaína; Clemente de Oliveira Neto, Laura; Alves Ramos Zin, Elisa; Pedro Pinto Perez, Antônio; Faria Zima, Giulia; Poliana da Silva Oliveira, Keyla; Francisco Santos da Silva, Gustavo; Miguel Fernandes Wouters, João; da Silva Franchini, Rafael; Gonçalves Vidal, Clara; Jezini Bittencourt, Nicole; et al. (Brazilian Journal of Implantology and Health Sciences, 2025)
This research sought articles, reviews, descriptive studies, cohort studies, and medical record analysis, whose theme brought a survey of the most recent studies in the literature regarding fecal calpronectin (FC) cutoff values ​​indicative of clinical remission for Idiopathic Ulcerative Colitis (UC). FC was presented during this review as a potential biomarker of clinical, endoscopic, and histological remission in patients with UC. In addition, some studies have shown that the use of FC in patients being monitored for UC resulted in lower costs to the system when compared to requesting follow-up colonoscopies.